Seminar dan Pelatihan “Belajar Jarak Jauh Dengan E-Learning bagi Mahasiswa STIE Krakatau” - Yustianto, Benny Prakarsa (Penerbit Goodwood, 2024)
Purpose: This community service program aimed to improve the ability of students at STIE Krakatau to use e-learning effectively for distance learning, adapt to diverse learning styles, and increase engagement in online classes. Methodology/approach: The activity was conducted through a three-hour seminar and workshop held in the computer laboratory at STIE Krakatau. The development of an adaptive e-learning model follows the engineering approach (analysis, design, implementation, evaluation). The tools used included multimedia authoring software and online questionnaires to assess students' visual, auditory, and kinesthetic learning styles. Results/findings: The training resulted in a prototype adaptive e-learning model capable of adjusting content delivery based on students’ learning styles. Ongoing evaluations indicate improved understanding and interaction in the online learning environment. Conclutions: This program successfully introduced adaptive e-learning to STIE Krakatau students, improving their engagement and understanding of distance learning. The developed model adjusted the content to different learning styles, showing its potential to enhance the quality of online education. Broader testing is recommended to validate its effectiveness on a larger scale in the future. Limitations: The study only implemented alpha testing and involved a limited number of participants; thus, broader testing and future experimental studies are required for generalization. Contribution: This program provides practical solutions for higher-education institutions transitioning to online learning. It contributes to educational technology development, particularly in designing adaptive e-learning for diverse learners.